Evaluation and management of ketosis-prone diabetes. Issue 1 (2nd January 2019) - Gaba, Ruchi; Mehta, Paras; Balasubramanyam, Ashok
ABSTRACT: Introduction : Patients presenting with diabetic ketoacidosis (DKA) who lack the classic phenotype of autoimmune type 1 diabetes have become increasingly identified in recent decades. This has led to the recognition of heterogeneous syndromes of 'ketosis-prone diabetes' (KPD). Evaluation and optimal management of KPD differs from that of 'typical' type 1 or type 2 diabetes. Awareness of these differences and a systematic approach to diagnosis and treatment can improve glycemic control and prevent both acute and chronic complications of diabetes. Areas covered : This article reviews the Aß classification scheme ('A' for autoantibody status and 'ß' for beta cell functional reserve) which accurately delineates subgroups of KPD, and addresses the relevance of defining these subgroups for clinical outcomes and long-term insulin dependence. Subsequently, the detailed evaluation and management of KPD patients after their index DKA episode is described. Expert commentary : Among patients presenting with DKA, it is important to diagnose specific subgroups of KPD and not assume that they represent exclusively patients with autoimmune type 1 diabetes. The Aß classification is an accurate aid to diagnosis, and permits optimal management of the subgroups (e.g., insulin treatment for the ß- subgroups; follow-up testing and a range of treatment options for the ß+ subgroups).